The consequences of key audit matters on users: A literature review - Pais, C. (2020 15th Iberian Conference on Information Systems and Technologies (CISTI), 2020)
There is an information gap between what users expect on an audit and what an audit is, and the new audit report is made to reduce this information gap, by changing its structure and content. Among other changes, the new audit report includes a new section for the disclosure of key audit matters (KAM) which is mandatory in Union European (UE) on June 2016 and in the United States (US) on June 2019. This change, triggered manly by the 2008 financial crisis, is expect a positive effect on audit quality or users’ perception of it. The main objective of this paper is review the literature of this recent topic on the perspective of users and market reaction. The results of the influence of disclosure KAM in the audit report on users and market reaction are mixed. Some and experimental studies in Canada and in the US settings, on investors and financial analysts, find a positive influence of disclosure KAM on the audit quality perception, which is not find in German setting on bank directors. When it comes to archival papers, there is not found any investor reaction to disclosure KAM.